Understanding the evolutionary potential of epigenetic variation: a comparison of heritable phenotypic variation in epiRILs, RILs, and natural ecotypes of Arabidopsis thaliana - Zhang, Yuan-Ye; Latzel, Vit; Fischer, Markus; Bossdorf, Oliver (Heredity, 2018)
Increasing evidence for epigenetic variation within and among natural plant populations has led to much speculation about its role in the evolution of plant phenotypes. However, we still have a very limited understanding of the evolutionary potential of epigenetic variation, in particular in comparison to DNA sequence-based variation. To address this question, we compared the magnitudes of heritable phenotypic variation in epigenetic recombinant inbred lines (epiRILs) of Arabidopsis thaliana-lines that mainly differ in DNA methylation but only very little in DNA sequence-with other types of A. thaliana lines that differ strongly also in DNA sequence. We grew subsets of two epiRIL populations with subsets of two genetic RIL populations, of natural ecotype collections, and of lines from a natural population in a common environment and assessed their heritable variation in growth, phenology, and fitness. Among-line phenotypic variation and broad-sense heritabilities tended to be largest in natural ecotypes, but for some traits the variation among epiRILs was comparable to that among RILs and natural ecotypes. Within-line phenotypic variation was generally similar in epiRILs, RILs, and ecotypes. Provided that phenotypic variation in epiRILs is mainly caused by epigenetic differences, whereas in RILs and natural lines it is largely driven by sequence variation, our results indicate that epigenetic variation has the potential to create phenotypic variation that is stable and substantial, and thus of evolutionary significance.
Keywords: ekotyp; DNA, Plant; Ecotype; Quantitative Trait, Heritable; Arabidopsis; biologická evoluce; genetická variace; DNA rostlinná; Biological Variation, Population; epigeneze genetická; populační genetika; Genetics, Population; Epigenesis, Genetic; Biological Evolution; biologická variabilita populace; kvantitativní znak dědičný; DNA Methylation; metylace DNA; Genetic Variation